Collaboration in Nuclear Science and Technology: Prospects and Challenges for Pakistan’s Regulator - Noreen Iftakhar; Hamid Saeed Raza (CISS Insight Journal, 2025)
A nuclear regulator cannot be complacent due to the peculiar nature of its job. The regulator continuously strives to be the best and a role model for others. However, this persistent striving for excellence requires several factors. Among these factors, the most important is the collaboration with its peers and other organizations at the international level, in the sharing of knowledge, information, feedback, experience, and capacity building. Pakistan, being the pioneer member of the International Atomic Energy Agency (IAEA), has a long history of cooperation with the international community. Pakistan Nuclear Regulatory Authority (PNRA) was established in 2001 as the national nuclear regulatory authority, in compliance with the Convention on Nuclear Safety (CNS) - through the promulgation of PNRA Ordinance, i.e., Ordinance III of 2001. It was assigned the responsibility to regulate all nuclear installations, radiation facilities, and associated activities in Pakistan for the protection of workers, the general public, and the environment. PNRA, like other international Regulatory Bodies (RBs) in the nuclear domain, has developed mechanisms for international collaboration to bring its performance and processes at par with the international standards. PNRA regularly participates in global nuclear forums and bilateral as well as multilateral arrangements, assigns experts to participate in international activities, and also presents itself for peer review. Despite these efforts, Pakistan faces certain challenges related to international cooperation. Alongside, PNRA also faces several complications while achieving its mission and vision. These primarily include limited access to codes and standards for ensuring nuclear safety, technology denials, and international emphasis on Pakistan’s defense initiatives, which sometimes limits the visibility of its efforts and achievements in the peaceful applications of nuclear technology. Against this backdrop, this paper offers two sets of proposals to overcome these challenges, both at the regulatory and policy level.